Penilaian Indeks Kematangan Digital Rekam Medis Elektronik di Klinik X - Ari Sukawan; Bhakti Aryani; Dony Setiawan Hendyca Putra; Diana Barsasella; Yuliani Yuliani (Politeknik Negeri Jember, 2026)
Digital transformation in the healthcare sector has become an urgent priority to improve service quality and operational efficiency. A key component of this transformation is the implementation of Electronic Medical Records (EMRs), as mandated by the Indonesian Minister of Health Regulation No. 24 of 2022 and supported by the 2024 Health Digital Transformation Blueprint. Clinic X began implementing EMRs in late 2023 but continues to face challenges, including limited system features, synchronization issues with the Satu Sehat platform, and server disruptions. This study evaluated the clinic’s digital maturity using the Digital Maturity Index (DMI) to formulate strategic recommendations. A mixed-methods approach with a concurrent triangulation strategy was employed through observations, in-depth interviews, and questionnaires based on the official DMI instrument developed by the Indonesian Ministry of Health. The results showed that Clinic X achieved an average maturity level of 3 in Primary Care Readiness, Information System Capability and Infrastructure, and Data Security. The clinic demonstrated strengths in staff digital literacy and infrastructure but weaknesses in governance guidelines and EMR feature development. Overall, the clinic is at the developing stage, indicating the need to strengthen system integration, infrastructure, and information governance to accelerate digital transformation.